Study on relationship between elderly sarcopenia and inflammatory cytokine IL-6, anti-inflammatory cytokine IL-10 - Rong, Yu-Dong; Bian, Ai-Lin; Hu, Hui-Ying; Ma, Yue; Zhou, Xin-Zi (BMC geriatrics, 2018)
The pathophysiological mechanism of sarcopenia in the elderly has not yet been fully understood. Here, we aim to explore the relationship between sarcopenia and the inflammatory cytokine interleukin-6 (IL-6), and the anti-inflammatory cytokine interleukin-10 (IL-10) in an elderly population. Our study comprised 118 males and 46 females aged between 61 and 90 who had received a general medical examination in Tianjin First Central Hospital. Subjects were divided into a sarcopenia group and a non-sarcopenia group, defined according to the criteria of the Asian Working Group for Sarcopenia (AWGS). We compared body composition, handgrip strength (HS), gait speed (GS), biochemical indexes, levels of IL-6 and IL-10, living habits, and disease status between these groups. Non-sarcopenia subjects undertook more regular physical exercise than sarcopenia patients. Sarcopenia subjects had higher nutrition risk but lower body mass index (BMI), serum albumin (ALB), triglyceride (TG), and creatinine (Cr) levels compared to non-sarcopenia subjects. Sarcopenia subjects were older and had higher visceral fat tissue (VFA) than non-sarcopenia subjects (P < 0.05), along with higher IL-6 and IL-10 levels. Furthermore, IL-6/IL-10 ratios were higher in subjects with sarcopenia (P < 0.05). Age, BMI, levels of physical activity, nutritional risk, VFA, IL-6, IL-10, IL-6/IL-10 ratio were independently associated with the presence of sarcopenia in univariate regression analyses. Following adjustment for confounding factors, the presence of sarcopenia was positively correlated with IL-6, IL-10, IL-6/IL-10 ratio and inversely correlated with BMI. Age is associated with increased presence of sarcopenia. The levels of inflammation cytokine IL-6, anti-inflammatory IL-10 and IL-6/IL-10 ratio were increased in elderly sarcopenia subjects. Sarcopenia was associated with increased levels of inflammatory cytokine IL-6, anti-inflammatory cytokine IL-10, and IL-6/IL-10 ratios.